Inversores monofásicos para conexão de sistemas fotovoltaicos à rede - Marangoni, Filipe (2012)
This research presents a comparative study of single-phase transformerless grid connected inverters, employing photovoltaic generators. Initially is highlighted the increasing worldwide demand for electricity and the growth of the use of renewable sources, driving the development of these technologies. It is also presented an overview of the photovoltaic decentralized power generation, including the major types of systems and their connection to the utility grid. In order to reduce the electricity cost of photovoltaic generation, the elimination of low frequency transformer that connects the inverter to the grid, was presented as an interesting alternative. But associated with the direct inverter connection, leakage currents may arise due to the existence of parasitic capacitances between the panel photovoltaic cell and the system ground. To avoid these problems, several modifications in the electronic circuit of the inverter have been proposed to eliminate variations in the inverter common mode voltage. This research evaluates some of these topologies in order to define performance parameters that can serve as the basis for choosing a topology over the other for a set of specifications such as the installed power or the amplitude of grid voltage, among others.